(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Intensification is a pervasive linguistic phenomenon that enhances the emotive, evaluative, and emphatic dimensions of communication. In English, intensification is predominantly realized through lexical devices that modify the degree, force, or focus of a proposition. This paper explores intensification as a pragmatic and semantic strategy, investigating its forms, functions, and distributions across various registers. The study adopts a corpus-based methodology and provides a detailed literature review of intensification mechanisms in English. Findings show that intensifiers are not merely redundant modifiers but serve crucial interpersonal and discourse functions. Through examining authentic examples and frequency data, this study contributes to a deeper understanding of how intensification operates in contemporary English.